2010
DOI: 10.1099/ijs.0.014977-0
|View full text |Cite
|
Sign up to set email alerts
|

Labrys wisconsinensis sp. nov., a budding bacterium isolated from Lake Michigan water, and emended description of the genus Labrys

Abstract: Labrys wisconsinensis sp. nov., a budding bacterium isolated from Lake Michigan water, and emended description of the genus Labrys Two facultatively anaerobic, budding bacterial strains, designated W1215-PCA4 T and SRNK-1, were isolated from water from Lake Michigan, USA. The two strains showed identical ERIC-PCRgenerated genomic fingerprints and shared 99.9 % 16S rRNA gene sequence similarity. Strain W1215-PCA4 T showed highest 16S rRNA gene sequence similarities to Labrys monachus VKM B-1479 T (95.8 %), Labr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…The major fatty acids and quinone of DCY64 T are in good agreement with those of member of the genus Labrys (Islam et al , 2007). The polar lipids patterns of DCY64 T and three reference type strains in this study are consistent with those described as part of a previous study by Albert et al (2010). Major amounts of phosphatidylmonomethylethanolamine, phosphatidylglycerol, phosphatidylcholine and diphosphatidylglycerol, minor to trace amounts of phosphatidyldethanolamine, phosphatidyldimethylethanolamine, two unidentified aminolipids, three unidentified aminophospholipids, four unidentified phospholipids and two unidentified polar lipids were detected in the polar lipids pattern of strain DCY64 T (Fig.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…The major fatty acids and quinone of DCY64 T are in good agreement with those of member of the genus Labrys (Islam et al , 2007). The polar lipids patterns of DCY64 T and three reference type strains in this study are consistent with those described as part of a previous study by Albert et al (2010). Major amounts of phosphatidylmonomethylethanolamine, phosphatidylglycerol, phosphatidylcholine and diphosphatidylglycerol, minor to trace amounts of phosphatidyldethanolamine, phosphatidyldimethylethanolamine, two unidentified aminolipids, three unidentified aminophospholipids, four unidentified phospholipids and two unidentified polar lipids were detected in the polar lipids pattern of strain DCY64 T (Fig.…”
supporting
confidence: 91%
“…The three phylogenetic analysis methods () clearly showed that DCY64 T clustered within the group containing members of the genus Labrys . This cluster was supported by a 100 % bootstrap value that is consistent with the results of previous studies (Miller et al , 2005; Islam et al , 2007; Chou et al , 2007; Carvalho et al , 2008; Albert et al , 2010). However, DCY64 T formed a monophyletic branch in this group.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…They reported that Betaproteobacteria predominated, followed by Bacteroidetes and Alphaproteobacteria. There are however, no published reports that characterized the microbial community in Lake Michigan potable water, although Albert et al (2010Albert et al ( , 2013Albert et al ( , 2014 have reported the isolation of several novel bacterial species and a novel genus of bacteria from Lake Michigan potable water.…”
mentioning
confidence: 99%